Effects of ICT Connectedness, Permeability, Flexibility, and Negative Spillovers on Burnout and Job and Family Satisfaction - Leung, Louis (Human Technology, 2011)
This study investigates the effects of information and communication technologies (ICTs), permeability, flexibility, and spillovers of work into home and home into work on job burnout and job and family satisfaction. Results from a random sample of 612 office workers show that individuals who reported being satisfied with their jobs tended to feel that the Internet could help them accomplish work-related tasks, that traditional media could help them relax after work, and had a highly permeable boundary between their home domain and a highly flexible work environment. On the other hand, people who experienced low job satisfaction faced high work spillovers into home life and high burnout. The findings underscore that the connectedness of ICTs is not the main issue for assessing the consequences associated with ICTs. Rather, individual control over what passes through the boundaries shapes the consequences people experience.